Gender, Power, and Regional Political Hegemony: A Critical Framing Analysis of Sherly Tjoanda’s Representation in North Maluku Online Media - Julaiha Hi Amin (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
This study analyzes how local online media frames female leadership within the nexus of gender relations and regional political hegemony, focusing on the news coverage of Sherly Tjoanda Laos on Nuansamalut.com. Employing a qualitative approach with Pan and Kosicki’s critical framing analysis model, this research examines four major news articles published during the first three months post-inauguration (February-May 2025), interpreted through the lenses of Gramscian hegemony and gender theories. The findings reveal a systematic transformation of framing across four distinct phases: gender symbolization, technocratic leadership construction, policy breakthrough legitimation, and the consolidation of moral authority. Critically, this study demonstrates that the representation of female leadership transcends traditional stereotypes, shifting toward the construction of "technocratic femininity" a legitimacy anchored in administrative capacity and policy performance which paradoxically operates within the framework of central power hegemony. This study offers a novel theoretical contribution by deconstructing the concept of technocratic femininity within the conceptualization of localized gender politics. Practically, it serves as a critical evaluative guide for local media to move beyond acting as consensus-production agents for dominant power structures, and instead become drivers of transformative gender emancipation within regional democracy.